2021
DOI: 10.1093/tbm/ibab021
|View full text |Cite
|
Sign up to set email alerts
|

Blood cancer caregiving during COVID-19: understanding caregivers’ needs

Abstract: The COVID-19 pandemic likely exacerbated caregiving challenges for caregivers of parents diagnosed with a blood cancer. Providing care during a public health crisis presents a complex web of uncertainties regarding cancer care, personal health, and COVID-19 risk. Identifying caregivers’ uncertainty experiences during the COVID-19 pandemic can be a first step in learning where to direct resources or alter policies to ensure that they can not only perform their caregiver role but also cope in health-promoting wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 29 publications
3
45
0
1
Order By: Relevance
“…Study findings indicated that carers’ psychological wellbeing deteriorated during the pandemic. Frequently cited psychological concerns included fear (Carballo et al., 2021; Cohen et al., 2020; D’herde et al., 2021; Fisher et al., 2021; Ng et al., 2020; Simblett et al., 2021; West et al., 2021), depression (Altieri & Santangelo, 2020; Giebel et al., 2021; Li et al., 2021; Pongan et al., 2021; Rainero et al., 2021), anxiety (Borelli et al., 2021; Carcavilla et al., 2021; Consonni et al., 2021; Giebel et al., 2021; Hwang et al., 2021; Li et al., 2021; Ng et al., 2020; Pongan et al., 2021; Rainero et al., 2021; Salari et al., 2020; West et al., 2021; Zucca et al., 2021), stress/distress (Alexopoulos et al., 2021; Carballo et al., 2021; Cohen et al., 2020; Dhavale et al., 2020; Fisher et al., 2021; Longacre et al., 2021; Rainero et al., 2021; Rusowicz et al., 2021; Tam et al., 2021; Zucca et al., 2021), sleep disturbances (Azevedo et al., 2021; Carcavilla et al., 2021; Li et al., 2021) and dietary issues (Borelli et al., 2021; Carcavilla et al., 2021; Li et al., 2021; Makaroun et al., 2021; West et al., 2021). Increased psychological burdens were often linked to a reduction in support (Budnick et al., 2021; Lee et al., 2021; Macchi et al., 2021; Tsapanou et al., 2021), or a deterioration in the care recipient's health (Borelli et al., 2021; Yasuma et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study findings indicated that carers’ psychological wellbeing deteriorated during the pandemic. Frequently cited psychological concerns included fear (Carballo et al., 2021; Cohen et al., 2020; D’herde et al., 2021; Fisher et al., 2021; Ng et al., 2020; Simblett et al., 2021; West et al., 2021), depression (Altieri & Santangelo, 2020; Giebel et al., 2021; Li et al., 2021; Pongan et al., 2021; Rainero et al., 2021), anxiety (Borelli et al., 2021; Carcavilla et al., 2021; Consonni et al., 2021; Giebel et al., 2021; Hwang et al., 2021; Li et al., 2021; Ng et al., 2020; Pongan et al., 2021; Rainero et al., 2021; Salari et al., 2020; West et al., 2021; Zucca et al., 2021), stress/distress (Alexopoulos et al., 2021; Carballo et al., 2021; Cohen et al., 2020; Dhavale et al., 2020; Fisher et al., 2021; Longacre et al., 2021; Rainero et al., 2021; Rusowicz et al., 2021; Tam et al., 2021; Zucca et al., 2021), sleep disturbances (Azevedo et al., 2021; Carcavilla et al., 2021; Li et al., 2021) and dietary issues (Borelli et al., 2021; Carcavilla et al., 2021; Li et al., 2021; Makaroun et al., 2021; West et al., 2021). Increased psychological burdens were often linked to a reduction in support (Budnick et al., 2021; Lee et al., 2021; Macchi et al., 2021; Tsapanou et al., 2021), or a deterioration in the care recipient's health (Borelli et al., 2021; Yasuma et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Despite their greater mental health needs, carers of those with intellectual disabilities received less social support (Willner et al., 2020). As a result of the reduced support measures, carers reported feeling socially isolated and lonely (Amaniera et al., 2021; Azevedo et al., 2021; Carbone et al., 2021; Fisher et al., 2021; Makaroun et al., 2021; Tam et al., 2021; West et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that although the COVID-19 pandemic has altered many aspects and logistics of HSCT and recovery, 9 , 12 it has not worsened pre-HSCT distress, fatigue, or QOL compared to before the pandemic. Indeed, well established factors such as patients’ illness experience, treatment burden, uncertainty regarding future health and potential HSCT complications are still likely the driving force behind distress, fatigue, and QOL challenges in this population.…”
Section: Discussionmentioning
confidence: 60%
“… 11 Hence, pandemic restrictions on lifestyle and travel may have negatively impacted the size and effectiveness of social support networks for HSCT recipients, intensifying their distress. 12 …”
Section: Introductionmentioning
confidence: 99%